2014
DOI: 10.1002/jobm.201300925
|View full text |Cite
|
Sign up to set email alerts
|

tert‐Butyl hydroperoxide‐induced differing plasma membrane and oxidative stress processes in yeast strains BY4741 and erg5Δ

Abstract: The molecular mechanism of tert-butyl hydroperoxide (t-BuOOH) elicited cytotoxicity and the background of t-BuOOH sensitivity were studied in the Saccharomyces cerevisiae ergosterol-less gene deletion mutant erg5Δ and its parental strain BY4741. In comparison to BY4741, untreated erg5Δ cells exhibited alterations in sterol and fatty acid compositions of the plasma membrane, as reflected by the inherent amphotericin B resistance, an elevated level (31%) of plasma membrane rigidity and a decreased uptake of glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The previously described protocol was adapted for peroxide [36,37] and superoxide anion radicals [34,38] with modifications. A positive control, Me (0.5 mmol/L as end concentration), C Pe , C T80 , C Et , Van (bacteria), and Cas (fungi) at their respective MEC 10 concentrations were used to treat the cell suspensions (~10 6 cells/mL) for an hour at 35 °C (bacteria) and 30 °C (fungi) in RPMI media.…”
Section: Methodsmentioning
confidence: 99%
“…The previously described protocol was adapted for peroxide [36,37] and superoxide anion radicals [34,38] with modifications. A positive control, Me (0.5 mmol/L as end concentration), C Pe , C T80 , C Et , Van (bacteria), and Cas (fungi) at their respective MEC 10 concentrations were used to treat the cell suspensions (~10 6 cells/mL) for an hour at 35 °C (bacteria) and 30 °C (fungi) in RPMI media.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies utilizing chemical derivatives of AmB, membrane permeabilisation assays, ergosterol-binding assays, and nuclear magnetic resonance spectroscopy, have indicated that AmB mycotoxicity is relayed primarily through sequestration of ergosterol into cell surface aggregates (Anderson et al, 2014;Gray et al, 2012;Palacios, Dailey, Siebert, Wilcock, & Burke, 2011). Strains deficient in Erg5 (and to a much lesser extent Erg2, Erg4, or Erg6) have increased tolerance to AmB (Gazdag et al, 2014). It is plausible that in the strains with enhanced polyene tolerance, the drug has reduced affinity for the sterols present.…”
Section: Tolerance To Mycotoxic Compoundsmentioning
confidence: 99%
“…Overexpression of AhpF and AhpC in the t ‐butyl hydroperoxide treated cells was confirmed by SDS‐PAGE (data not shown). It has been reported that in S. cerevisiae incubated with t ‐butyl hydroperoxide the intracellular O 2 •− concentration was magnified 6.7‐fold in comparison to that of untreated yeast cells , and this treatment has influenced on the rigidity and fluidity of plasma membrane of Schizosaccharomyces pombe plasma membrane . Therefore, similar studies on the investigation of the level of O 2 •− and components of plasma membrane of E. coli with and without AhpCF overexpression upon treatment with t ‐butyl hydroperoxide are required in the future.…”
Section: Resultsmentioning
confidence: 99%
“…•À concentration was magnified 6.7-fold in comparison to that of untreated yeast cells [14], and this treatment has influenced on the rigidity and fluidity of plasma membrane of Schizosaccharomyces pombe plasma membrane [15]. Therefore, similar studies on the investigation of the level of O 2 •À and components of plasma membrane of E. coli with and without AhpCF overexpression upon treatment with t-butyl hydroperoxide are required in the future.…”
Section: Resultsmentioning
confidence: 99%